Analisis kemampuan literasi statistik calon guru matematika ditinjau berdasarkan adversity quotient - Nalisa, Ayang Insan; Nugraha, Yandika (Jurnal of Math Tadris, 2024)
This study aims to describe the statistical literacy skills of prospective mathematics teachers in terms of Adversity Quotient (AQ). This study uses a qualitative descriptive research method. The subjects of this study came from 100 prospective mathematics teachers from UIN Mataram. The selection of subjects was based on the results of the adversity quotient questionnaire with the climber, camper and quitter types and students who tend to be able to master statistical literacy based on the results of problem-solving tests. Data collection techniques used adversity quotient questionnaires, statistical literacy test instruments and task-based interviews. While data analysis refers to the statistical literacy framework. The results of this study are that there is no significant difference between the statistical literacy skills of the climber, camper, and quitter types. All three are able to understand and present data well. The difference between these three types lies in the ability of each type to interpret data and communicate data, both verbally and in writing.